Taking Confucian ethics seriously : contemporary theories and applications - Yu, Kam-por, 1957-; Tao, Julia Lai Po-Wah, 1946-; Ivanhoe, P. J. (SUNY series in Chinese philosophy and culture., 2010)
This thought-provoking work presents Confucianism as a living ethical tradition with contemporary relevance. While acknowledged as one of the world's most influential philosophies, Confucianism's significance is too often consigned to a historical or solely East Asian context. Discussing both the strengths and weaknesses of Confucian ethics, the volume's contributors reflect on what this tradition offers that we cannot readily learn from other systems of ethics. Developing Confucian ethical of ideas within a contemporary context, this work discusses the nature of virtue, the distinction between public and private, the value of spontaneity, the place of sympathy in moral judgment, what it means to be humane, how to handle competing values, and the relationship between trust and democracy. for all those concerned with ethics, this book offers both new perspectives and resources for the ongoing consideration of how we should live. --Book Jacket.